The Effect of Social Cohesion on Interest, Usefulness, and Ease of Use of a Driving Assistance System in Older Adults - Hiroko Kamide (MDPI AG, 2021)
This study examined the relationship between social cohesion and the perceived interest in, the usefulness of, and the ease of use of an instructor-based driver assistance system in a sample of older adults. With the aging of the population, the use of technologies to support the driving skills of the elderly is expected, and it is necessary to clarify the conditions under which the elderly will be interested in these advanced technologies. Traditionally, social cohesion has been focused on as a function of instrumental and practical support in the lives of the elderly. Since social cohesion reflects the intention to help each other, it could be an opportunity to provide information on advanced driving skill techniques to older people who are becoming more difficult to drive. As an initial exploration, this study examined whether social cohesion was associated with the interest in, the usefulness of, and the ease of use of an instructor-based driver assistance system in 150 elderly people. The results showed that a greater social cohesion was significantly associated with these evaluations, and that a comprehension of the system also contributed. The possession of a license was significantly associated with interest in the program. These findings are an essential step toward the understanding of the roles of social cohesion and positive perception of advanced technology in older adults.